PENGGUNAAN MODUL TEORI GRAPH BERBASIS MASALAH UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN HASIL BELAJAR MAHASISWA - Marlina, Leni; Juliangkary, Eliska; Yuliyanti, Sri (Media Pendidikan Matematika, 2019)
This research is motivated by problems where the books used by students during the lecture process only refer to one textbook as a source of reading. Textbooks that are difficult to understand make students not understand the concept. In addition, students experience many misconceptions. As a result, student learning outcomes are also low. The purpose of this study was to describe the use of problem-based graft theory modules to improve understanding of students’ concepts and learning outcomes. This research method is a class action research method consisting of two cycles. The instrument used in this study is a concept understanding test as well as a test of learning outcomes. The subjects of this study were the 6th semester B grade students of Mathematics Education Department of FPMIPA IKIP Mataram consisting of 34 students. The results of this study indicate that student learning outcomes have increased. In the first cycle student learning outcomes reached 63% and in the second cycle to 79. In addition, the concept of understanding students experienced a percentage increase of 65% (sufficient category) in the first cycle to 75% (high category) in the second cycle. Thus, it can be concluded that the use of problem-based graph theory modules can improve understanding of concepts and learning outcomes of mathematics education students at IKIP Mataram